Barriers to timely tympanostomy tube placement in trisomy 21. (January 2021) - Bachrach, Kevin; Bains, Ashank; Shehan, Jennifer N.; Levi, Jessica R.
Abstract: Objectives: Trisomy 21 is the most common chromosomal abnormality in the United States with an incidence of 1 in 700 in live-born children. Children with trisomy 21 are at increased risk for chronic ear disease, as well as other medical issues that may complicate healthcare access. In this study, we investigate whether children with trisomy 21 experience delays in tympanostomy tube insertion, and if there are any factors that contribute to a delay in care. Methods: We performed a retrospective analysis on patients with trisomy 21 undergoing tympanostomy tube insertion at Boston Medical Center between 2005 and 2019 by analyzing the electronic medical record. This cohort was matched to patients without trisomy 21 by age, gender, surgery date and surgeon. The primary outcome was time elapsed between surgery decision date and date of tympanostomy tube insertion. Results: A total of 20 patients with trisomy 21 underwent tympanostomy tube insertion at Boston Medical Center between 2005 and 2019. The trisomy 21 cohort was matched to 39 patients in the general population. The average time elapsed from decision to undergo surgery to tympanostomy tube insertion was 43.1 days in the general population and 119.0 days in the trisomy 21 cohort (p < .01). Conclusion: Patients with trisomy 21 experience greater delays in tympanostomy tube insertion than the general population, which may be due to the increased burden of comorbid conditions in people with trisomy 21. Highlights: The trisomy 21 cohort experienced significantly longer delays in tympanostomy tube insertion than the general population. There was a 2.5 month delay in tympanostomy tube insertion in the trisomy 21 cohort. The rate of surgery deferral and cancellation was not significantly different across cohorts.